Serial or Parallel Metastasis of Cutaneous Melanoma? A Study of the German Central Malignant Melanoma Registry - Gassenmaier, Maximilian; Eigentler, Thomas Kurt; Keim, Ulrike; Goebeler, Matthias; Fiedler, Eckhard; Schuler, Gerold; Leiter, Ulrike; Weide, Benjamin; Grischke, Eva-Maria; Martus, Peter; Garbe, Claus (Journal of Investigative Dermatology, 2017)
For more than a century the Halstedian hypothesis of contiguous metastasis from the primary tumor through the lymphatics to distant sites shaped lymph node surgery for melanoma. We challenge this dogma of serial metastatic dissemination. A single-center series of 2,299 patients with cutaneous metastatic melanoma was investigated to analyze overall survival and distant metastasis-free survival of stage IV patients with or without primary lymphatic metastasis. Results were then compared with those of 2,134 patients from three independent centers of the German Central Malignant Melanoma Registry. A multivariate binary logistic regression model was used to identify risk factors for the initial metastatic pathway. Distant metastasis-free survival (hazard ratio = 1.02; 95% confidence interval = 0.91-1.14; P = 0.76) and overall survival (HR = 1.09; 95% CI = 0.96-1.23; P = 0.177) did not differ between stage IV patients with primary hematogenous or primary lymphatic metastasis. Melanoma localization was the only significant risk factor for the initial metastatic pathway. These findings indicate that regional and distant metastases originate from the primary tumor itself in a rather parallel than serial fashion and could explain the lack of survival benefit associated with immediate complete lymph node dissection in sentinel lymph node-positive melanoma patients.
EVALuna2:34312